More than meets the eye - Johansen, Iris; Johansen, Roy (Johansen, Iris. Kendra Michaels series., 2023)
"Serial killer James Michael Barrett leads a grim parade of police officers, FBI agents, and forensics into the woods of Pine Valley, forty-five miles east of San Diego. At the end of the second week of his high-profile murder trial, he has struck a plea deal with the prosecution: he'll reveal the location of his last victim's body in exchange for the D.A. taking the death penalty off the table. As they reach the site, a light rain begins to fall, and Barrett points to the spot. They swing the shovels down and hear a strange metallic sound. BOOM! A terrific explosion rocks the woods, killing Barrett and most of the officers instantly. One of the victims is FBI agent Cynthia Strode, a friend of Kendra Michaels. An even closer friend, Special Agent Roland Metcalf, is still alive but in critical condition. Kendra joins the crowd of law enforcement personnel at the hospital but waiting around isn't her style. She must figure out how the killer did it. It's the beginning of a case with many twists and turns. As the pace of murders accelerates, agent-for-hire Adam Lynch joins Kendra in the pursuit, and they get help from local college student (and Olympic hopeful) Tricia Walton, the only one of Barrett's targeted victims to survive her encounter. The recovering Agent Metcalf also lends a hand, but the killer has a target closer than any of them realize...and a terrifying plan they're only just beginning to understand"--